India : Economic Reform and Growth - Hemming, Richard (Occasional Papers; Occasional Paper ;, 1995)
This paper explores the Indian adjustment program of 1991/92 and its initial results. The contents include long-term growth trends for output, investment, and macroeconomic condition; education, labor employment, and poverty; growth, accumulation, and productivity; results of India-specific studies; the stabilization and adjustment strategy; the response to the reforms; the impact on unemployment and poverty; the behavior of private investment; fiscal adjustment and reform; recent experience with a surge in capital inflows: overall trends, the investor base, comparison with other countries, and factors behind the flows; the impact on the economy; the sustainability of capital flows; and structural reforms and the implications for investment and growth; trade reform; the investment regime; public enterprise reform; and financial market reform.